Matlab codes of Subset Simulation for reliability analysis and structural optimization - Li, Hong-Shuang; Cao, Zi-Jun (Structural and multidisciplinary optimization, 2016)
This paper presents two efficient and compact Matlab codes of Subset Simulation for reliability analysis and structural optimization. The codes for reliability analysis and structural optimization comprise of the direct Monte Carlo and Markov Chain Monte Carlo. The theoretical and numerical elements of Subset Simulation are briefly presented in this paper, as well as the detailed instructions to implement the standard codes for solving reliability analysis and structural optimization problems. The paper also discusses simple extensions of argument check, post-processing, alternative stop criterion and constraint-handling. Four examples are presented to demonstrate these codes, two for reliability analysis and two for structural optimization. This paper will be helpful for the students and newcomers both in reliability analysis and structural optimization to understand and use Subset Simulation. The complete codes are included in Appendixes 1 and 2 , and they can be downloaded from https://sites.google.com/site/rasosubsim/ .